Expanding Radical SAM Chemistry by Using Radical Addition Reactions and SAM Analogues. Issue 39 (30th August 2016) - Ji, Xinjian; Li, Yongzhen; Xie, Liqi; Lu, Haojie; Ding, Wei; Zhang, Qi
Abstract: Radical S ‐adenosyl‐l ‐methionine (SAM) enzymes utilize a [4Fe‐4S] cluster to bind SAM and reductively cleave its carbon–sulfur bond to produce a highly reactive 5′‐deoxyadenosyl (dAdo) radical. In almost all cases, the dAdo radical abstracts a hydrogen atom from the substrates or from enzymes, thereby initiating a highly diverse array of reactions. Herein, we report a change of the dAdo radical‐based chemistry from hydrogen abstraction to radical addition in the reaction of the radical SAM enzyme NosL. This change was achieved by using a substrate analogue containing an olefin moiety. We also showed that two SAM analogues containing different nucleoside functionalities initiate the radical‐based reactions with high efficiencies. The radical adduct with the olefin produced in the reaction was found to undergo two divergent reactions, and the mechanistic insights into this process were investigated in detail. Our study demonstrates a promising strategy in expanding radical SAM chemistry, providing an effective way to access nucleoside‐containing compounds by using radical SAM‐dependent reactions. Abstract : SAM switch‐up : The SAM‐dependent enzyme NosL was shown to switch from hydrogen abstraction to radical addition reaction when using an olefin‐containing substrate analogue. Two SAM analogues with different nucleosides are able to initiate the radical‐based reactions comparable to SAM, offering a way to expand SAM‐dependent reactions and access new nucleoside‐containing compounds.